Spanking and subsequent behavioral problems in toddlers: A propensity score-matched, prospective study in Japan. (July 2017) - Okuzono, Sakurako; Fujiwara, Takeo; Kato, Tsuguhiko; Kawachi, Ichiro
Abstract: Harsh or frequent spanking in early childhood is an established risk factor for later childhood behavioral problems as well as mental disorder in adulthood in Western societies. However, few studies have been conducted in Asian populations, where corporal punishment is relatively accepted. Moreover, the impacts of occasional spanking on subsequent behavioral problems remain uncertain. This study sought to investigate prospectively the association between the frequency of spanking of toddlers and later behavioral problems in Japanese children using national birth cohort data. We used data from the Longitudinal Survey of Newborns in the 21st Century, a population-based birth cohort data set collected by the Japanese Ministry of Health, Labour, and Welfare (N = 29, 182). Frequency of spanking ("never", "sometimes" and "always") and child behavioral problems were assessed via a caregiver questionnaire when the child was 3.5 years old and again at 5.5 years. Propensity score matching was used to examine the association between frequency of spanking and child behavioral problems, adjusting for parental socioeconomic status, child temperament and parenting behaviors. Compared to children who were never spanked, occasional spanking ("sometimes") showed a higher number of behavioral problems (on a 6-point scale) (coefficient: 0.11, 95% CI: 0.07–0.15), and frequent spanking ("always") showed an even larger number of behavioral problems compared with "sometimes" (coefficient: 0.08, 95% CI:0.01–0.16). Spanking of any self-reported frequency was associated with an increased risk for later behavioral problems in children.